2010
DOI: 10.1007/s00784-009-0379-9
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning ability and induced dentin loss of a magnetostrictive ultrasonic instrument at different power settings

Abstract: Some laboratory studies have evaluated the oscillation mode of ultrasonic scalers. None of them recorded its influence on calculus removal and quantified dental hard tissue loss. This study aimed to compare the performance of a magnetostrictive ultrasonic instrument at different power settings in vitro in relation to the tip oscillation activity. The oscillation activity of the straight Slimline® insert in the Cavitron® ultrasonic scaling device was analyzed at five different power settings with the help of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…However, this placement did not guarantee similar working performance due to differences in working principles. In previous studies, it was confirmed that the higher the output power of the scaler is, the more effective it is 30 . Therefore, it is possible that the output power of the magnetostrictive scaler is greater than that of the piezoelectric scaler.…”
Section: Discussionmentioning
confidence: 78%
“…However, this placement did not guarantee similar working performance due to differences in working principles. In previous studies, it was confirmed that the higher the output power of the scaler is, the more effective it is 30 . Therefore, it is possible that the output power of the magnetostrictive scaler is greater than that of the piezoelectric scaler.…”
Section: Discussionmentioning
confidence: 78%
“…The in vitro evaluation of substance loss of dental tissue has been described by various investigators using different periodontal treatment methods . All of the periodontal treatment methods used in this study have demonstrated the removal of cementum, although AP alone eliminated less cementum than HC or U.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Bless et al . found that rougher surfaces occurred after treatment with ultrasonic scalers when compared to treatment with hand curettes. The SEM results of this study have shown that smoother root surfaces can be obtained with HC when compared to U.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation